Investigation of Residual Stresses Induced by Milling of Compacted Graphite Iron by x-ray Diffraction Technique - Kara, Mehmet Emre; Kuzu, Ali Taner; Bakkal, Mustafa (Springer Science and Business Media LLC, 2023)
We are thankful for the support received from The Scientific and Technological Research Council of Türkiye. This study investigates the relationship between residual stresses, cutting parameters, and machining performance in the milling process of compacted graphite iron (CGI). X-ray diffraction (XRD) analysis is employed to measure residual stresses on the cast and milled surfaces, while cutting force modeling is utilized to calculate the tangential force, power, and active work. The results demonstrate that tensile residual stresses are predominant on the milled surfaces, attributed to the both mechanical and thermal loads generated during milling. By analyzing various cutting conditions, it is observed that lower feeds contribute to reduced plastic deformation, resulting in lower residual stress levels. Additionally, higher cutting speeds lead to higher temperatures, but due to the shorter machining time, heat accumulation is limited, resulting in higher residual stresses, especially at low feeds. At high feeds, residual stresses decreased as the cutting speed increased. The interplay between cutting parameters and residual stresses highlights the need for optimizing cutting conditions to enhance fatigue strength in CGI components. These findings provide valuable insights for process optimization and quality control in the milling of CGI materials. Türkiye Bilimsel ve Teknolojik Araştırma Kurumu Publisher's Version
Keywords: Optimization; X-ray diffraction techniques; Turning; Residual stress; Stress-induced; Compacted graphite iron; Quality control; X ray diffraction analysis; Milled surfaces; X-ray diffraction; Residual stresses; Cutting; Cutting speed; Graphite; Cutting conditions; Cutting machining; Milling (machining); Milling; Machining performance; Cutting parameters